2020
DOI: 10.1542/neo.21-2-e98
|View full text |Cite
|
Sign up to set email alerts
|

Updates on Assessment and Monitoring of the Postnatal Growth of Preterm Infants

Abstract: Assessing and monitoring the physical growth of preterm infants is fundamental to NICU care. The goals of nutritional care are to approximate the growth and body composition of the healthy fetus and to support optimal brain development while minimizing future cardiometabolic risk. Both poor and excessive growth predict adverse long-term health outcomes. Growth curves are clinical tools used to assess the preterm infant’s growth status. Several growth curves for preterm infants were developed in the past decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 53 publications
1
20
0
5
Order By: Relevance
“…When looking at growth of preterm children in general, there can be big challenges for optimizing infant growth. 8,42 In childhood, even moderately preterm children continue to be smaller (both in height and weight), 4 but in puberty there seem not to be notable problems according to our findings. For teenagers themselves, developing normally and at the same time as others can have a large psychological lift.…”
Section: Discussionsupporting
confidence: 64%
“…When looking at growth of preterm children in general, there can be big challenges for optimizing infant growth. 8,42 In childhood, even moderately preterm children continue to be smaller (both in height and weight), 4 but in puberty there seem not to be notable problems according to our findings. For teenagers themselves, developing normally and at the same time as others can have a large psychological lift.…”
Section: Discussionsupporting
confidence: 64%
“…Regardless of the definition used, PGF and moderate to severe malnutrition among extremely preterm infants were consistently associated with growth rates below 13 g/kg/day. Our finding that growth rates are strongly correlated with declines in weight z scores indicates that analyzing changes in weight z scores (i.e., malnutrition) instead of analyzing single-time weight z scores (i.e., PGF) ( 19 ) or calculating growth rates ( 21 ) could be justified. Without using the term “malnutrition”, other studies have analyzed the association between changes in weight z scores from birth to 36 weeks PMA and neurodevelopment ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 91%
“…Many support the use of the INTEGROWTH-21 st growth curves because they were developed using longitudinal data from mother-infant dyads of geographically diverse backgrounds who had reliable gestational ages, proper nutrition, and good medical care ( 14 ). Others question the validity of these curves for assessing infants less than 30 weeks because the number of preterm infants that contributed to the development of the INTERGROWTH-21 st growth curves was limited ( 19 ). Our comparative analysis showed that the INTERGROWTH-21 st growth curves were more predictive of cognitive outcomes than the Fenton growth curves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 , 11 This evidence suggests that any nutritional intervention that reduces the risk of postnatal growth faltering should ideally improve the quantitative (i.e., weight, length, and head circumference) and qualitative (i.e., body composition) outcomes of growth. 12 , 13 Body composition measurements are not part of routine clinical care, but reference values for preterm infants have been recently defined. 14 …”
Section: Introductionmentioning
confidence: 99%